The majesty of the judiciary - Krishna Iyer, V. R., 1915- (New Delhi : Universal Law Pub. Co., 2007)
Articles on judges, judicial reforms, constitutional law, death sentence, arbitration, and jurisprudence
Includes bibliographical references
Keywords: Justice, Administration of -- India; Water supply -- India; Judges -- India -- Biography